2009
DOI: 10.1103/physrevb.80.235321
|View full text |Cite
|
Sign up to set email alerts
|

Three-level mixing and dark states in transport through quantum dots

Abstract: We consider theoretically the transport through the double quantum dot structure of the recent experiment of C. Payette et al. [Phys. Rev. Lett. 102, 026808 (2009)] and calculate stationary current and shotnoise. Three-level mixing gives rise to a pronounced current suppression effect, the character of which charges markedly with bias direction. We discuss these results in connexion with the dark states of coherent population trapping in quantum dots.PACS numbers: 73.63. Kv, 73.50.Td, 73.23.Hk In a recent e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Our observations can help toward the general engineering and understanding of coupling and consequent mixing between many quantum levels in coupled QD systems, and the dark state is a useful tool for quantum coherent phenomena in transport involving multiple quantum levels. [48][49][50][51][52]54 Lastly, a number of directions for future investigation are clear: ͑i͒ although the discussion in the second half of this paper has focused on three-level mixing, mixing at two-level and four-level crossings is also of potential interest, and our mixing Hamiltonian model, initially developed for threelevel mixing, can easily be adapted to study these cases. ͑ii͒ The strength of the couplings ͑C parameters͒ at any given level crossing could not be altered for the two devices discussed in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations can help toward the general engineering and understanding of coupling and consequent mixing between many quantum levels in coupled QD systems, and the dark state is a useful tool for quantum coherent phenomena in transport involving multiple quantum levels. [48][49][50][51][52]54 Lastly, a number of directions for future investigation are clear: ͑i͒ although the discussion in the second half of this paper has focused on three-level mixing, mixing at two-level and four-level crossings is also of potential interest, and our mixing Hamiltonian model, initially developed for threelevel mixing, can easily be adapted to study these cases. ͑ii͒ The strength of the couplings ͑C parameters͒ at any given level crossing could not be altered for the two devices discussed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…47 Clearly, strong suppression of the resonant current in one branch and the associated dark state formation is a genuine and robust effect originating from three-level mixing. Furthermore, the suppression of an otherwise strong resonance due to destructive interference represents an all-electrical QD analog [48][49][50][51][52] of coherent population trapping in a three-level system of quantum and atom optics when two of the three couplings are dominant. We note that all-optical coherent population trapping has recently been demonstrated in self-assembled InAs QDs.…”
Section: Analysis Of Coherent Mixing At a Three-level Crossingmentioning
confidence: 99%
“…[9][10][11][12][13] Illuminating recent theoretical work by Emary and coworkers also examines three level intra-dot mixing leading to dark-state formation specifically with our vertical double dot structure in mind. 37) …”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22] Double quantum dot (DQD) systems such as GaAs/AlGaAs [4][5][6] or Si/SiO 2 are also candidates for realizing three-level systems and have been theoretically investigated. 23,24) Tokura et al 12) theoretically investigated resonant tunneling currents under locally different Zeeman energies and found that when the magnetic fields in each QD are non-collinear, four resonant peaks can be observed. Ke et al 23) constructed density matrix equations and investigates the relation between the phase of the driving lasers and transport properties.…”
Section: Introductionmentioning
confidence: 99%